The Relationship Self Control and Student Hedonism Behavior and Its Implications for Guidance and Counseling - Silviani Sari; Yusri Yusri (Counseling and Humanities Review, 2021)
This research is motivated by the phenomenon that there are adolescents who have low self-control and high hedonism. It can be seen that students lie to their parents to send money on the grounds of buying necessities on campus when in fact it is for fun and buying things that are not needed and it is difficult to control themselves to carry out a hedonistic lifestyle. Some even expect Bidikmisi scholarships to buy what they want instead of buying necessities for college or shopping for daily food. This study aims to (1) describe the control of students, (2) describe the hedonistic behavior of students, (3) examine the relationship between self-control and hedonistic behavior of students. This research is a type of quantitative research with a correlational descriptive method. The population in this study of 1906 students of the Faculty of Education, Padang State University, enrolled in 2018 with a sample of 295 people. The instrument used in collecting research data was a questionnaire with a choice of answers using a Likert scale model. The analysis used is a descriptive analysis of percentages and uses the Pearson Product Moment technique with the help of the SPSS For Windows 20.0 program. The results of the study revealed that (1) students' self-control was in a low category. (2) students' hedonistic behavior is in the moderate category, and (3) there is a significant negative relationship self-control and student hedonistic behavior. Based on the research findings, it is highly recommended that students increase self-control and carry out positive and productive activities. and avoiding hedonistic behavior.